ANALISIS KINERJA PEGAWAI UPT BLK DINAS SOSIA ANALISIS KINERJA PEGAWAI UPT BLK DINAS SOSIA ANALISIS KINERJA PEGAWAI UPT BLK DINAS SOSIAANALISIS KINERJA PEGAWAI UPT BLK DINAS SOSIAANALISIS KINERJA PEGAWAI UPT BLK DINAS SOSIAANALISIS KINERJA PEGAWAI UPT BLK - Pratama, Abi Hardhiyan; Widowati, Nina (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Technical Implementation Unit of Vocational Training Centers Departement of Social Services Manpower and Transmigration in Kudus Regency in encouraging the creation of qualified manpower is needed to help the government reduce unemployment. Trained workforce is needed, especially in the era of technology. In order to improve the quality of the labor force Technical Implementation Unit of Vocational Training Centers Departement shall provide training to the youth. So that these objectives can be achieved the required performance quality organization. The phenomenon happens on the field is the quality of graduates Technical Implementation Unit of Vocational Training Centers Departement is not in accordance with the labor market. This is evidenced by the number of trainees who have not been trained to work though. Therefore, the need for assessment to assess the performance of employee Technical Implementation Unit of Vocational Training Centers Departement of Social Services Manpower and Transmigration in Kudus Regency and the factors that support performance. The purpose of this study is basically knowing Performance of Employee Analysis of Technical Implementation Unit of Vocational Training Centers Departement of Social Services Manpower and Transmigration in Kudus Regency. This study uses descriptive qualitative research. The data in this study were obtained from interviews with informants, observation and documents. The results of this study indicate that the performance of employee of Technical Implementation Unit of Vocational Training Centers Departement of Social Services Manpower and Transmigration in Kudus Regency existence of various types of programs that meet the needs of trainees, the development of both the instructor and the development of a network, related to surveillance has been good apart supervised by the organization above Technical Implementation Unit of Vocational Training Centers Departement of Social Services Manpower and Transmigration in Kudus Regency also conduct internal monitoring technological developments. Nevertheless, Technical Implementation Unit of Vocational Training Centers Departement of Social Services Manpower and Transmigration in Kudus Regency is still constrained by the limitations of employees in terms of quantity, limited budgets and a more adequate infrastructure to support the performance and accuracy of timing was good because of the activities to be delayed due to lack of participants.